First records of two species and two genera of ants (Hymenoptera: Formicidae) collected in a semi-urban area from Yucatan, Mexico - Cano-Ravell, Alan; Rosas-Mejía, Madai; Vásquez-Bolaños, Miguel; Ballina-Gómez, Horacio Salomón; Tuyin-Díaz, Ana Luz; Reyes-Solís, Guadalupe del Carmen (Revista Colombiana de Entomología, 2022)
First records of two ant species, i.e., Hypoponera opacior and Pseudomyrmex seminole, and two genera, i.e., Acanthosticus, Mycetosoritis, associated with decaying stages of necrotramps established in a semi-urban area of Yucatan, Mexico.